2022
DOI: 10.3390/jmse10030347
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Coastal Lagoons Review: Sites to Visit before Disappearance

Abstract: Coastal lagoons are an established priority habitat in the European environment because of the biological communities that inhabit them. Their origin is related to the transport of sediments from a nearby river or the movement of sands by the marine currents that produce the closure of a gulf. Therefore, they are recent geological formations, which also disappear quickly if environmental conditions change. The 37 coastal lagoons with a surface area greater than 10 km2 located in the Mediterranean basin have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
(74 reference statements)
0
4
1
Order By: Relevance
“…However, in our study, that model not only obtains a lower result (R 2 = 0.7189) but is surpassed by the R783 × R705/R490 model (R 2 = 0.7749), which was also evaluated in the Mar Menor, but with worse results (R 2 = 0.701). These differences are because the Mar Menor has a lower Chl-a and solids load than Albufera, as mentioned in the study by Soria et al [35]. Therefore, in the Mar Menor, the R705 band is more effective than R783, contrary to our case study, because of a greater influence of scattering in the NIR and the saturation of the visible bands due to the high load of suspended particles [32].…”
Section: Discussioncontrasting
confidence: 54%
“…However, in our study, that model not only obtains a lower result (R 2 = 0.7189) but is surpassed by the R783 × R705/R490 model (R 2 = 0.7749), which was also evaluated in the Mar Menor, but with worse results (R 2 = 0.701). These differences are because the Mar Menor has a lower Chl-a and solids load than Albufera, as mentioned in the study by Soria et al [35]. Therefore, in the Mar Menor, the R705 band is more effective than R783, contrary to our case study, because of a greater influence of scattering in the NIR and the saturation of the visible bands due to the high load of suspended particles [32].…”
Section: Discussioncontrasting
confidence: 54%
“…Coastal lagoons are shallow water bodies generally separated from the open sea by a sandy bar, characterised by low water renewal ratios due to their limited water exchange with the sea and reduced freshwater inputs ( Soria et al, 2022 ). According to the Habitats Directive of the European Union ( EU, 1992 ), coastal lagoons are threatened sites declared as a priority for environmental protection, as they support ecosystems that are very vulnerable to hydrological alterations, water pollution and habitat loss ( Pérez-Ruzafa et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coastal lagoon areas exemplify the conflict of interest between the development of human activities and the ecological requirements of aquatic ecosystems ( Flower and Thompson, 2009 ). Soria et al (2022) identified thirty-seven coastal lagoons with a surface area larger than 10 km 2 in the Mediterranean region, and concluded that most of them showed eutrophication problems due to the pollution of their inflows. To cope with this issue, the European Green Deal developed a list of goals and actions to preserve biodiversity, reverse the environmental degradation and protect ecosystems ( EC, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the pronounced gradients of, and fluctuations in, physical and chemical conditions of brackish waters, they are considered to be naturally highly stressed ecosystems (Elliott & Quintino, 2007; Teichert et al, 2017). In addition, low average depths and close connectivity to the adjacent terrestrial ecosystems have made many brackish waters and their fish populations vulnerable to over‐fishing (Haimovici & Cardoso, 2017; Jackson et al, 2001; Ulman et al, 2020), climate change (Kashkooli et al, 2017; MacKenzie et al, 2007), eutrophication (Karadurmuş & Sari, 2022; Soria et al, 2022; Table 1), pollution (Barletta et al, 2019; Islam & Tanaka, 2004), and species invasions (Daskalov & Mamedov, 2007; Feyrer et al, 2003). These anthropogenic impacts have, in recent decades, resulted in significant declines of economically and ecologically important brackish water fish populations in, for instance, the Black Sea (Demirel et al, 2020; Oguz, 2017), Caspian Sea (Daskalov & Mamedov, 2007), Marmara Sea (Demirel et al, 2022), brackish lakes and lagoons (Haimovici & Cardoso, 2017; Mohanty et al, 2009), and certain major river estuaries (Shan et al, 2013; Zhou et al, 2019).…”
Section: Introduction To Brackish Water Environmentsmentioning
confidence: 99%